Reportage And Framing The Link Between Climate Change And Biodiversity In The Philippine Daily Inquirer In 2012 - Domingo, Dhanicca Amor M.; Barroga-Jamias, Serlie (Silliman Journal, 2022)
This study determines the reportage and framing of news linking both climate change and biodiversity by the leading national daily, Philippine Daily Inquirer. A total of 326 online articles from the archives of www.inquirer.net from June to October 2012 were content analyzed for length, presence of graphics or audio or video clips, treatment, and section placement. ‘Frames’ or the themes used by the writers to present the issue were surfaced through open and thematic coding. The research was guided by framing, the second-level of the Agenda Setting Theory by Maxwell McCombs and Donald Shaw (1972). Only 79 (24.23%) directly linked climate change with biodiversity. These articles were predominantly presented as straight news stories under the news section of the newspaper with an average of 100 to 500 words per article. Writers used seven frames to discuss the interlinked issues, namely (in order): biodiversity for climate change; human survival; cost of biodiversity; twin environmental challenges; call to action; survival of ecosystems; and survival of species. Only a few articles used the frame ‘call to action’ or specifically pointed to the need for laws, policies, or social movements that would mitigate climate change and arrest biodiversity loss. Climate change affecting biodiversity and vice-versa must be expounded more to make the public better understand and appreciate their interdependence. Given that both climate change and biodiversity are considered as environmental challenges that pose a lot of risks, media can also focus on framing articles that would motivate policy formulation and implementation about these interlinked issues.